GEOGRAPHICAL AND DIALECTAL DISTRIBUTION OF PLATEARIUS' LIBER DE SIMPLICI MEDICINA IN ENGLAND - Garrido Anes, Edurne (International Journal of English Studies, 2009)
This article aims to give an account of the sources from which we can draw some information concerning the geographical and dialectal distribution of Platearius' Liber de simplici medicina in England. The Latin copies and the Middle English renderings preserved as British holdings reveal dynamic and widespread dissemination of this treatise. Linguistic and extra-linguistic factors will help us find out the origin or dwelling place of some of the people who copied, read or owned an exemplar of the work. Dialectal features and toponymical references found in the exemplars will be taken into account alongside some legal and library records.